BioMEMS : science and engineering perspectives - Bădilescu, Simona; Packirisamy, Muthukumaran (CRC Press/Taylor & Francis, 2011)
"As technological advancements widen the scope of applications for biomicroelectromechanical systems (BioMEMS or biomicrosystems), the field continues to have an impact on many aspects of life science operations and functionalities. Because BioMEMS research and development require the input of experts who use different technical languages and come from varying disciplines and backgrounds, scientists and students can avoid potential difficulties in communication and understanding only if they possess a skill set and understanding that enables them to work at the interface of engineering and biosciences.Keeping this duality in mind throughout, BioMEMS: Science and Engineering Perspectives supports and expedites the multidisciplinary learning involved in the development of biomicrosystems. Divided into nine chapters, it starts with a balanced introduction of biological, engineering, application, and commercialization aspects of the field. With a focus on molecules of biological interest, the book explores the building blocks of cells and viruses, as well as molecules that form the self-assembled monolayers (SAMs), linkers, and hydrogels used for making different surfaces biocompatible through functionalization. The book also discusses: Different materials and platforms used to develop biomicrosystems Various biological entities and pathogens (in ascending order of complexity) The multidisciplinary aspects of engineering bioactive surfaces Engineering perspectives, including methods of manufacturing bioactive surfaces and devices Microfluidics modeling and experimentation Device level implementation of BioMEMS concepts for different applications. Because BioMEMS is an application-driven field, the book also highlights the concepts of lab-on-a-chip (LOC) and micro total analysis system (ơTAS), along with their pertinence to the emerging point-of-care (POC) and point-of-need (PON) applications"--Anotace od vydavatele
Keywords: biologické mikroelektromechanické systémy; bioinženýrství; biological microelectromechanical systems; bioengineering; monografie; monographs